2019
DOI: 10.1186/s13058-019-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of screening mammography by density and texture: a cohort study from a population-based screening program in Denmark

Abstract: Background Screening mammography works better in fatty than in dense breast tissue. Computerized assessment of parenchymal texture is a non-subjective method to obtain a refined description of breast tissue, potentially valuable in addition to breast density scoring for the identification of women in need of supplementary imaging. We studied the sensitivity of screening mammography by a combination of radiologist-assessed Breast Imaging Reporting and Data System (BI-RADS) density score and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 17 publications
2
39
1
1
Order By: Relevance
“…The calculated diagnostic indices in our study did not completely match those reported in a cohort study performed by Von Euler-Chelpin et al [17] on 54,997 participants. In this study, they compared the sensitivity and specificity of mammography as compared to breast density.…”
Section: Discussioncontrasting
confidence: 99%
“…The calculated diagnostic indices in our study did not completely match those reported in a cohort study performed by Von Euler-Chelpin et al [17] on 54,997 participants. In this study, they compared the sensitivity and specificity of mammography as compared to breast density.…”
Section: Discussioncontrasting
confidence: 99%
“…Estimates of program sensitivities range from 75 -100 % for women with non-dense breasts, 69 -82 % for women with heterogeneously dense breasts, and 47 -84 % for women with extremely dense breasts (3,137,139,140). A similar trend has also been shown using Volpara TM for density stratification (141).…”
mentioning
confidence: 56%
“…In considering personalized screening, it should, however, be taken into account that the screening test itself is probably the best available tool to discriminate between high and low risk women. In the present nationwide Danish screening program with its "one-size-fits-all" biennial screening of women aged 50-69 years, the 2-year risk of breast cancer was 80 times higher in screen-positive than in screen-negative women [44]. In comparison, the ability of personalized screening models to discriminate between low and high risk women is 0.51-0.80, which is between none and moderate [45].…”
Section: Public Health Implicationsmentioning
confidence: 81%